PEREMPUAN PENCARI NAFKAH DALAM PRESPEKTIF HADIS - Maraulang, Maraulang; Ismail, La Ode (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: The role of women as breadwinners is a significant topic in modern Islamic studies. In Islamic tradition, while men are generally regarded as the primary breadwinners, numerous hadiths support women's involvement in the family's economy. This research evaluates and interprets the hadiths concerning women as breadwinners and their application in modern life. Through a literature review of the hadiths, it is found that Islam permits women to work and make a living as long as they adhere to Sharia law and continue to fulfill their duties as homemakers. This research also highlights how the dual role of women can positively contribute to the family's economy and address the challenges they face. Family support, community, as well as governmental and corporate policies, are crucial in assisting women to balance their roles as breadwinners and homemakers. The conclusion of this study indicates that Islam not only allows but also values the contribution of women to the family economy, demonstrating flexibility and balance in Islamic teachings. Keywords: Women, Breadwinners, Hadith Perspective